2019
DOI: 10.1088/1742-6596/1351/1/012074
|View full text |Cite
|
Sign up to set email alerts
|

RADEC: An Alternative Learning Of Higher Order Thinking Skills (HOTs) Students Of Elementary School on Water Cycle

Abstract: One of the strengths of the RADEC learning model is that learning focuses on teaching and problem-solving skills, so in other words, RADEC is a learning model that can develop students’ Higher Order Thinking Skills (HOTS). Learning steps of RADEC consisted of 5 steps which were very easy to remember because they were in accordance with the name of the learning model itself, namely: (1) Read; (2) Answer (A); (3) Discuss (D); (4) Explane (Explain) and (5) Creat (C). At each step of learning RADEC, it can develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
2
7
0
9
Order By: Relevance
“…The mentoring activities provided can train the cognitive skills of teachers to train students' critical thinking. This finding is in line with the results of previous research, which showed that online mentoring in implementing RADEC learning model enhance teacher knowledge to train students' critical thinking (Handayani et al, 2019;Satria & Sopandi, 2019;Sopandi, 2019;Karlina et al, 2020;Setiawan et al, 2020).…”
Section: 326supporting
confidence: 91%
“…The mentoring activities provided can train the cognitive skills of teachers to train students' critical thinking. This finding is in line with the results of previous research, which showed that online mentoring in implementing RADEC learning model enhance teacher knowledge to train students' critical thinking (Handayani et al, 2019;Satria & Sopandi, 2019;Sopandi, 2019;Karlina et al, 2020;Setiawan et al, 2020).…”
Section: 326supporting
confidence: 91%
“…Selain itu, penelitian yang dilakukan oleh Pratama et al yang dapat disimpulkan bahwa model pembelajaran RADEC dapat meningkatkan kemampuan berpikir tingkat tinggi siswa di sekolah dasar yang dilihat berdasarkan skor rata-rata post-test kelas RADEC sebesar 70,08 yang dibandingkan dari skor rata-rata pretest sebesar 40,44 yang artinya terdapat peningkatan sebesar 29,54 (Pratama et al, 2020). Hal ini juga didukung oleh penelitian Handayani et al yang menyebutkan bahwa model RADEC sebagai alternatif model pembelajaran untuk meningkatkan HOTS (Handayani, Sopandi, Syaodih, Suhendra, & Hermita, 2019).…”
Section: Pendahuluanunclassified
“…Pembuatan produk tersebut tidak dibatasi oleh guru, dalam artian guru membebaskan siswa untuk mewujudkan ide kreatifnya dalam sebuah karya. Hal tersebut sejalan dengan penelitianHandayani et al (2019) yang menyimpulkan bahwa model pembelajaran RADEC dapat meningkatkan keterampilan berpikir kreatif siswa. Dengan demikian terdapat relevansi antara model RADEC dengan HOTS, yakni pada tahap Create kemampuan berpikir kreatif siswa akan mampu terbangun.…”
unclassified
“…Kemampuan berpikir pada siswa merupakan tahapan untuk melatih pengetahuan kognitif, yaitu: siswa mampu menganalisis, mengevaluasi, dan memberikan penilaian terhadap suatu fakta yang dipelajari dan bisa menggabungkan fakta dan ide, sehingga mampu menciptakan sesuatu yang baru berdasarkan apa yang sudah dipelajari (Annuuru et al, 2017). Berpikir kreatif juga dapat membuat siswa memiliki keterampilan, kemampuan menganalisis serta mampu berpikir tingkat tinggi (Handayani et al, 2019). Berpikir kreatif dapat diartikan sebagai kemampuan penyelesaian suatu masalah, manfaatnya dapat melatih siswa untuk berpikir lancar, luwes, dapat melakukan elaborasi dan memiliki daya cipta (Marliani, 2015).…”
Section: Berpikir Kreatifunclassified